Survey of teacher social competency - Jeki Haryanto; Salvetri Salvetri (Journal of Educational and Learning Studies, 2022)
The social competence of physical education teachers is still low and needs to be improved so that communication between teachers and students during learning takes place is better. The learning process that occurs in the classroom and outside the classroom should take place pleasantly, to realize this  skills in communicating with students are needed. This study aims to determine the level of social competence of sports teachers from the point of view of the principal's assessment. This needs to be known in order to add insight into the social competence of teachers from various existing points of view, so that understanding of the social competence of teachers can be more in-depth. Survey research was conducted to see the principal's assessment of the social competence of physical education  teachers. The population in this study were all public elementary school sports teachers in Kerinci Regency, amounting to 228 people. The sampling technique in this study used a simple random sampling technique so that 50 people were selected as samples. Data on the social competence of sports teachers in this study were collected using a questionnaire. The results of this study indicate that the level of social competence of physical education teachers based on the principal's assessment is in the fairly good category. So that physical education teachers, school principals, and the government need to make programs so that the social competence of sports teachers can be improved.